Analisis Potensi Ekonomi dan Prioritas Pengembangan Kakao Rakyat di Pulau Bangka - Sitorus, Rostiar; Zasari, Maera (Jurnal Ilmiah Manajemen Kesatuan, 2022)
This paper aims to analyze the potential for community cocoa development in Bangka Island by determining the main priority factors and calculating the economic potential of the people's cocoa. In determining priority factors using the Analytical Hierarchy Process (AHP) method, with 25 farmer respondents whose role is to provide views and determine alternative priority criteria as determinants of future cocoa development in this area. The results of the AHP analysis stated that the main priority as the basis for developing cocoa farming in the future is market security, the second priority is the dissemination of GAP and the third priority is the availability of superior seeds. The results of the analysis of the economic potential of people's cocoa explain that smallholder cocoa in Bangka Island will generate revenue of Rp. per hectare per year if it is cultivated properly.